Efforts to Improve Students' Communication Skills and Technological Literacy by Developing Google Sites Learning Media on Virus Material at Grade X - Khairunnisa; Muh. Amir Masruhim; Elsje T. Maasawet; Abdul Hakim; Krisnha P. Candra; Lambang Subagiyo (Postgraduate, University of Mataram, 2024)
This research aims to develop Google Sites learning media on the subject of class X viruses to improve the communication skills and technological literacy of State High School students in Samarinda. The type of research used is Research and Development (R&D) with the Sugiyono development model. Data collection techniques using questionnaires, interviews and tests. The data analysis technique used is quantitative and qualitative data analysis. The subjects in this research were 3 expert validators, namely media, language and materials experts, 1 educational practitioner who was a biology subject teacher and class discussing viruses. The validation results from 3 expert validators obtained a score of 81.97% in the very feasible category. The practicality assessment by the teacher received a score of 97.8% in the very practical category and the assessment by students obtained a score of 85.1% in the very practical category. The use of Google Sites learning media has a significant influence on student learning outcomes with the calculated t value obtained (0.00 < 0.05) with a score gain index of 0.77 in the high category which shows that Google Sites learning media is effective in increasing students' understanding of learning materials. The results of the communication skills assessment questionnaire obtained a score of 81% in the very good category and technological literacy skills received a score of 86% in the very good category.